The Media industry in the era of artificial intelligence mechanisms and impacts - Saida HIMEUR (Akofena, 2023)
Abstract: Explore the role of artificial intelligence in enhancing the personalization of media content, improving the user experience, and increasing audience engagement. The study also discusses the potential ethical challenges that arise when using artificial intelligence in the media industry and provides recommendations for how to address them. Through an in-depth analysis of case studies and industry trends, this study provides valuable insights into how artificial intelligence can be leveraged to improve the efficiency and effectiveness of media content production and distribution. Overall, the findings of this study suggest that artificial intelligence has the potential to revolutionize the media industry, and that organizations that invest in this technology are likely to have a competitive advantage in the increasingly crowded media landscape. Keywords: Artificial intelligence, mechanisms, impacts, media work